2020
DOI: 10.3390/agronomy10030430
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Rate Increase Not Required for No-Till Wheat in Cool and Humid Conditions

Abstract: An increased nitrogen (N) supply was proposed to avoid grain yield (GY) reductions and successfully implement conservation agriculture (CA). We investigated interactions effects of tillage system and N supply on winter wheat (Triticum aestivum L.) at two sites in the Swiss midlands with no (0 kg N ha−1) and high (150–160 kg N ha−1) N supply using 15N-labelled ammonium nitrate in selected treatments. Wheat’s GY, yield components, N related traits and soil mineral N content (Nmin) under conventional tillage (CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Few research suggested a need to increase N application rate in NT systems (Six et al, 2004). However, other research in cool and humid conditions did not find a need for increasing N rate for NT wheat (Herrera et al, 2020). These mixed reports raise the question that N rate for NT should be studied based on yield environment.…”
Section: Introductionmentioning
confidence: 98%
“…Few research suggested a need to increase N application rate in NT systems (Six et al, 2004). However, other research in cool and humid conditions did not find a need for increasing N rate for NT wheat (Herrera et al, 2020). These mixed reports raise the question that N rate for NT should be studied based on yield environment.…”
Section: Introductionmentioning
confidence: 98%